Expression of the plasminogen system in the physiological mouse ovary and in the pathological polycystic ovary syndrome (PCOS) state - Genia F. Burchall; Dodie S. Pouniotis; Helena J. Teede; Sanjeeva Ranasinha; Kirsty A. Walters; Terrence J. Piva (BMC, 2019)
Abstract Background The fibrinolytic system and its inhibitors play a number of roles, apart from their function in blood haemostasis and thrombosis, namely in ovarian folliculogenesis and in ovulation. Plasminogen is converted to active plasmin at the time of follicular rupture through a decrease in plasminogen activator inhibitor-1 (PAI-1) and an increase in plasminogen activators. Oligo−/anovulation and follicle arrest are key characteristics of PCOS, but studies evaluating fibrinolytic/proteolytic markers within human or animal PCOS ovaries are lacking. We aimed to investigate and compare the expression and distribution of the plasminogen system markers in PCOS and control ovaries. Methods A hyperandrogenised PCOS mouse model was used that mimics the ovarian, endocrine and metabolic features of the human condition. Immunohistochemistry and digital image analysis were used to investigate and compare fibrinolytic/proteolytic markers plasminogen, plasminogen/plasmin, tissue plasminogen activator, urokinase plasminogen activator and inhibitor PAI-1 in PCOS and control ovaries. Student's t-test was used to compare data sets for normally distributed data and Wilcoxon-Mann Whitney test for non-normally distributed data. Results We noted differences in the ovarian distribution of PAI-1 that was expressed throughout the PCOS ovary, unlike the peripheral distribution observed in control ovaries. Plasminogen was present in small follicles only in PCOS ovaries but not in small follicles of control ovaries. When we assessed and compared PAI-1 expression within follicles of different developmental stages we also noted significant differences for both the PCOS and control ovaries. While we noted differences in distribution and expression within specific ovarian structures, no differences were noted in the overall ovarian expression of markers assessed between acyclical PCOS mice and control mice at the diestrus stage of the estrous cycle. Conclusions Our novel study, that comprehensively assessed the fibrinolytic/proteolytic system in the mouse ovary, showed the expression, differential localisation and a potential role for the plasminogen system in the physiological mouse ovary and in PCOS. Androgens may be involved in regulating expression of the ovarian plasminogen system. Further studies evaluating these markers at different time-points of ovulation may help to further clarify both physiological and potential pathological actions these markers play in ovulatory processes distorted in PCOS.